Reconfiguration for the Maximum Dynamic Wrench Capability of a Parallel Robot - Lin, Chih-Jer; Chen, Chun-Ta (Applied sciences, 2016)
In this paper, a Stewart-platform robot with sliding lockable base joints is proposed for reconfiguration, and it addresses the determination of the optimal configuration for the prescribed motion with maximum allowable dynamic wrench capability subject to the constraints imposed by the kinematics and dynamics of the proposed reconfigurable architecture. The numerical results from the hierarchical optimization process allow us to investigate the effects of the base point locations on the maximum dynamic wrench capability. The effectiveness of the proposed algorithm is demonstrated in the improvement of the maximum allowable dynamic wrench capability of the reconfigurable Stewart-platform robot.